2003
DOI: 10.1073/pnas.0337659100
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of transplanted bone marrow cells to Purkinje neurons in human adult brains

Abstract: We show here that cells within human adult bone marrow can contribute to cells in the adult human brain. Cerebellar tissues from female patients with hematologic malignancies, who had received chemotherapy, radiation, and a bone marrow transplant, were analyzed. Brain samples were obtained at autopsy from female patients who received male (sex-mismatched) or female (sexmatched, control) bone marrow transplants. Cerebella were evaluated in 10-m-thick, formaldehyde-fixed, paraffin-embedded sections that encompas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
245
6
12

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 396 publications
(273 citation statements)
references
References 25 publications
10
245
6
12
Order By: Relevance
“…Nonetheless, in mice with a lethal recessive liver disease (tyrosinaemia), transplantation of wild type BMDCs restored liver function by cell fusion and rescued the mice from death 3, 9 , indicating that cell fusion can have beneficial effects. Here we report that chronic inflammation resulting from severe dermatitis or autoimmune encephalitis leads to robust fusion of BMDCs with Purkinje neurons and formation of hundreds of binucleate heterokaryons, a 10-100 fold higher frequency than previously reported 8,10,11,14 . Single haematopoietic stem cell transplants showed that the fusogenic cell is in the haematopoietic lineage and parabiosis experiments revealed that fusion can occur without irradiation.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…Nonetheless, in mice with a lethal recessive liver disease (tyrosinaemia), transplantation of wild type BMDCs restored liver function by cell fusion and rescued the mice from death 3, 9 , indicating that cell fusion can have beneficial effects. Here we report that chronic inflammation resulting from severe dermatitis or autoimmune encephalitis leads to robust fusion of BMDCs with Purkinje neurons and formation of hundreds of binucleate heterokaryons, a 10-100 fold higher frequency than previously reported 8,10,11,14 . Single haematopoietic stem cell transplants showed that the fusogenic cell is in the haematopoietic lineage and parabiosis experiments revealed that fusion can occur without irradiation.…”
mentioning
confidence: 59%
“…Such fusion events are not limited to rodents, but have also been observed in humans 10 . Purkinje neurons have extensive dendritic arbours with synapses to hundreds of thousands of other neurons.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…[42,43]. Ce mécanisme contribue effectivement au chimérisme observé après greffe de moelle osseuse dans des organes comme le cerveau [55,56] ou le foie [45,46]. Il semble que ce processus fusionnel suffise à lui seul à expliquer la restauration de la fonction hépatique des souris FAH -/-après greffe de moelle; ce ne serait pas le cas dans le cerveau, le muscle ou d'autres épithéliums, où un autre mécanisme interviendrait également; mais les difficultés techniques rencontrées dans l'évaluation de la ploï-die des noyaux incitent à la prudence.…”
Section: Cellules Souches Vraies Cellules Souches Virtuelles?unclassified